Correlation between time-dependent inhibition of human farnesyl pyrophosphate synthase and blockade of mevalonate pathway by nitrogen-containing bisphosphonates in cultured cells. - Räikkönen, J; Taskinen, M; Dunford, J; Mönkkönen, H; Auriola, S; Mönkkönen, J (2011)
A class of drugs successfully used for treatment of metabolic bone diseases is the nitrogen-containing bisphosphonates (N-BPs), which act by inhibiting the vital enzyme, farnesyl pyrophosphate synthase (FPPS), of the mevalonate pathway. Inhibition of FPPS by N-BPs results in the intracellular accumulation of isopentenyl pyrophosphate (IPP) and consequently induces the biosynthesis of a cytotoxic ATP analog (ApppI). Previous cell-free data has reported that N-BPs inhibit FPPS by time-dependent manner as a result of the conformational change. This associated conformational change can be measured as an isomerization constant (K(isom)) and reflects the binding differences of the N-BPs to FPPS. In the present study, we tested the biological relevance of the calculated K(isom) values of zoledronic acid, risedronate and five experimental N-BP analogs in the cell culture model. We used IPP/ApppI formation as a surrogate marker for blocking of FPPS in the mevalonate pathway. As a result, a correlation between the time-dependent inhibition of FPPS and IPP/ApppI formation by N-BPs was observed. This outcome indicates that the time-dependent inhibition of FPPS enzyme is a biologically significant mechanism and further supports the use of the K(isom) calculations for evaluation of the overall potency of the novel FPPS inhibitors. Additionally, data illustrates that IPP/ApppI analysis is a useful method to monitor the intracellular action of drugs and drug candidates based on FPPS inhibition.